2013
DOI: 10.1371/journal.pone.0074384
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of RUNX2 Transcriptional Activity Blocks the Proliferation, Migration and Invasion of Epithelial Ovarian Carcinoma Cells

Abstract: Previously, we have identified the RUNX2 gene as hypomethylated and overexpressed in post-chemotherapy (CT) primary cultures derived from serous epithelial ovarian cancer (EOC) patients, when compared to primary cultures derived from matched primary (prior to CT) tumors. However, we found no differences in the RUNX2 methylation in primary EOC tumors and EOC omental metastases, suggesting that DNA methylation-based epigenetic mechanisms have no impact on RUNX2 expression in advanced (metastatic) stage of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 76 publications
3
36
0
Order By: Relevance
“…33 Several reports have demonstrated that BMP7 transcriptionally induces Runt-related transcription factor 2 ( RUNX2 ) expression. 34, 35 Intriguingly, Wang et al 36 reported that in ovarian cancer cells RUNX2 gene silencing provides a sharp downregulation of NUPR1 , suggesting the existence of an interaction between these two transcription factors. Indeed, in our preliminary microarray analyses conducted using ≥1.5-fold selection criteria, we found that RUNX2 was downregulated in Hep3B cells upon NUPR1 suppression.…”
Section: Resultsmentioning
confidence: 99%
“…33 Several reports have demonstrated that BMP7 transcriptionally induces Runt-related transcription factor 2 ( RUNX2 ) expression. 34, 35 Intriguingly, Wang et al 36 reported that in ovarian cancer cells RUNX2 gene silencing provides a sharp downregulation of NUPR1 , suggesting the existence of an interaction between these two transcription factors. Indeed, in our preliminary microarray analyses conducted using ≥1.5-fold selection criteria, we found that RUNX2 was downregulated in Hep3B cells upon NUPR1 suppression.…”
Section: Resultsmentioning
confidence: 99%
“…Silencing of the RUNX2 is also confirmed to inhibit SGC7901 cell proliferation and promote apoptosis in gastric cancer [25]. Wang et al revealed that RUNX2 suppression of RUNX2 could inhibit epithelial ovarian carcinoma cell proliferation, migration and invasion [26]. Consistent with these findings, our results showed that knockdown of RUNX2 knockdown inhibited TE-1 and EC109 cell viability, repressed TE-1 cell migration and invasion, and induced TE-1 cell apoptosis in vitro and suppressed tumor formation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that are crucial during embryogenesis are often hijacked during cancer progression, and RUNX2 is not an exception. RUNX2 is increasingly recognized in cancer biology for its oncogenic properties and a large number of articles link the deregulation of RUNX2 expression with progression and metastasization of different types of epithelial tumors (1,(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). Regulation of RUNX2 may occur at multiple levels and through multiple signaling pathways.…”
Section: Introductionmentioning
confidence: 99%